THE CONCEPTS OF LONG LIFE EDUCATION AND EDUCATION FOR ALL: THEORY, IMPLEMENTATION AND DEVELOPMENT ANALYSIS - Atsira, Luthfia; Sepriyanti, Nana; Martin, Kustati (As-Sulthan Journal of Education, 2026)
This study examines two fundamental concepts in educational theory: Long Life Education and Education For All. Long Life Education emphasizes continuous learning throughout human life, from prenatal to death, encompassing formal, non-formal, and informal education. Education For All advocates for universal access to education regardless of social, economic, or demographic backgrounds. This research employs a literature review methodology, analyzing various educational theories, Islamic perspectives, and international declarations including the Jomtien (1990) and Dakar (2000) frameworks. Findings reveal that both concepts are deeply rooted in Islamic teachings, supported by constitutional mandates, and essential for human development in the modern era. The study concludes that integrating these concepts is crucial for creating inclusive, equitable, and continuous learning opportunities that address technological advancement, social change, and individual potential development